Influence of Fermented-Moutai Distillers' Grain on Growth Performance, Meat Quality, and Blood Metabolites of Finishing Cattle - Cheng, Qiming; Xu, Duhan; Chen, Yulian; Zhu, Mingming; Fan, Xueyin; Li, Maoya; Tang, Xiaolong; Liao, Chaosheng; Li, Ping; Chen, Chao (Frontiers in Veterinary Science, 2022)
The objective of this study was to evaluate the effect of a diet containing fermented-Moutai distillers' grain (FMDG) on the growth performance, meat quality, amino acid composition and blood metabolites of finishing cattle. Thirty cattle (2 years old; 237.55 ± 10.72 kg) were randomly assigned to one of three dietary rations: 0% FMDG (control), 15% FMDG (R1) and 30% FMDG (R2) (DM basis). After 60 days, the inclusion of FMDG had no significant (p > 0.05) effects on growth performance indices (dry matter intake, average daily gain and feed efficiency), meat quality (cooking yield, shear force, L*, a*, and b* values) or bovine blood biochemical indicators (except albumin and immunoglobulin A). Cattle fed R1 had the lowest (p = 0.001) loin eye area. The inclusion of FMDG significantly (p < 0.05) increased the contents of various amino acids (except isoleucine and arginine) in beef as compared with the control. In particular, the diet with R2 significantly increased (p < 0.05) the contents of total amino acids, essential amino acids, nonessential amino acids and umami amino acids in beef, while the difference in bitter amino acid content between different treatments was not significant (p = 0.165). These results suggest that an appropriate amount of FMDG (15-30% DM) in the diets of finishing cattle had no detrimental impact on growth performance, meat quality or blood metabolites, but could alter the amino acid composition and proportion.